2008
DOI: 10.1111/j.1753-6405.2008.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

The physical health status of young Australian offenders

Abstract: Aims: To describe the socio-economic background and physical health status of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…As expected, our findings that older age is a predictor of self-reported poor health is in accordance with other studies [16,23,24]. The finding that young prisoners are prone to evaluate their health more positively than those older is confirmed by Butler et al, who reported that 91% of offenders aged 15-24 in Australia evaluated their health as "excellent", "very good", or "good" [25]. Moreover, psychological conditions are also associated with perceived poor health and these factors are well documented risk factors for both poor health status and incarceration.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, our findings that older age is a predictor of self-reported poor health is in accordance with other studies [16,23,24]. The finding that young prisoners are prone to evaluate their health more positively than those older is confirmed by Butler et al, who reported that 91% of offenders aged 15-24 in Australia evaluated their health as "excellent", "very good", or "good" [25]. Moreover, psychological conditions are also associated with perceived poor health and these factors are well documented risk factors for both poor health status and incarceration.…”
Section: Discussionsupporting
confidence: 93%
“…; Butler et al . ). In Australia, incarcerated populations score well below the general population on measures of health‐related functioning (Department of Justice ; Butler et al .…”
Section: Introductionmentioning
confidence: 97%
“…In Australia, incarcerated populations score well below the general population on measures of health‐related functioning (Department of Justice ; Butler et al . ). Studies in Australia and elsewhere indicate that people with intellectual disability (ID) are over‐represented in prisoner populations (Denkowski & Denkowski ; Hayes & Mcilwain ; Cockram ) with prevalence estimates ranging from 2% to 40% depending on methodological and diagnostic frameworks (Holland et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The age constitutes an important factor. Older inmates report a lower level of general health compared to younger prison population [3,14,[63][64][65]. On the contrary, younger prisoners report lower self-reported mental health status in contrast to older inmates [66].…”
Section: Discussionmentioning
confidence: 75%